Carbon Sequestration in Drylands - Lal, R (Annals of Arid Zone, 2016)
Drylands occupy 40% of the earth's surface and are prone to land degradation> by different processes. Desertification, a vague and qualitative term, implying degradation of soil and vegetation due to anthr9pogenic activity, reportedly affects 3.6 billion ha of the drylands. Although desertification is most severe in sub-Saharan Africa, the problem is not confined to the developing countries and is also prevalent in arid and semi-arid regions of North America, Australia, and parts of Europe. Degradation of soil and vegetation leads to emission of greenhouse gases (e.g .• C02, CH4, N20) to,the atmosphere. In contrast, improvement of soil quality through adoption of restorative measures can lead to increase in soil organic carbon content, improvement in biomass productivity, and mitigation of the greenhouse effect. Technological options for soil and vegetation restoration depend on ecozone characteristics' and need to be validated and fine-tuned for site-specific situations. Restorative technologies include introducing appropriate plant species adopted to harsh environments, controlling erosion and reclaiming salt-affected soils, adopting water harvesting techniques and efficient irrigation systems. The potential of C sequestration of such measures may be 30 to 200 kg ha-I y"1 ,depending on soil and ecozone characteristics. Identification of "trigger spots" may be necessary to set in motion the restorative process. While the potential of C sequestration in drylands may be high (0.9"1.9 Pg y"\ realization of even a fraction of this potential requires a coordinated effort at national and international ,levels. Development of a policy that involves participation of farmers and land managers is crucial in this endeavor.